2005
DOI: 10.1038/sj.bjc.6602480
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression fingerprint of uterine serous papillary carcinoma: identification of novel molecular markers for uterine serous cancer diagnosis and therapy

Abstract: Uterine serous papillary cancer (USPC) represents a rare but highly aggressive variant of endometrial cancer, the most common gynecologic tumour in women. We used oligonucleotide microarrays that interrogate the expression of some 10 000 known genes to profile 10 highly purified primary USPC cultures and five normal endometrial cells (NEC). We report that unsupervised analysis of mRNA fingerprints readily distinguished USPC from normal endometrial epithelial cells and identified 139 and 390 genes that exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
94
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 30 publications
4
94
0
Order By: Relevance
“…26,27 It has been shown that HER-2/neu oncoprotein overexpression is significantly associated with poor survival in uterine serous carcinoma 28 and could also be important as a predictive factor in uterine serous carcinoma treatment. It has been related to resistance to chemotherapy and poor prognosis in patients with this aggressive uterine malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 It has been shown that HER-2/neu oncoprotein overexpression is significantly associated with poor survival in uterine serous carcinoma 28 and could also be important as a predictive factor in uterine serous carcinoma treatment. It has been related to resistance to chemotherapy and poor prognosis in patients with this aggressive uterine malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…HER-2/neu overexpression in uterine serous carcinoma provides a biological rationale for the use of trastuzumab in the treatment of this malignancy. 27,30,31 A novel rabbit monoclonal antibody directed against HER2/neu oncoprotein SP3 was recently introduced and is used in routine clinical diagnosis in our laboratory. We have shown that using this novel antibody for HER2/neu testing reduces the rate of equivocal immunohistochemical results and highly correlates with HER2/neu gene amplification.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to an increased mRNA or protein stability. CLDN-3 and CLDN-4 are upregulated in ovarian and uterine cancers, 10,17,35,36 and CLDN-4 expression has been exploited for therapeutic purposes. 24 CLDN-7 expression is decreased in breast carcinomas, 13,37 but Adenocarcinoma vs bronchial cell (n ¼ 6) upregulated in gastric carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown an altered expression of CLDNs in human tumors, including tumors of the gastrointestinal tract, 8,9 ovary, 10 pancreas, 11 breast, 12,13 epidermis, 14 liver, 15,16 uterus 17 and prostate. 18 Little information is available on the expression of cytoplasmic tight junction proteins in human cancers, [19][20][21][22] and only one study has been published about the immunohistochemical localization of a tight junction protein (occludin (OCLN)) in lung tumors.…”
mentioning
confidence: 99%
“…6,20 Subsequent studies pointed to the involvement of DIRAS3 in the pathogenesis of a broader spectrum of human neoplasms, including pancreatic and thyroid cancers as well as lung, prostate, and endometrial carcinoma cell lines. [21][22][23][24][25] To date, DIRAS3 had not been studied for aberrations in human gliomas, though glial tumors with oligodendroglial differentiation exhibit frequent deletions of 1p (up to 80% of oligodendrogliomas and up to 50% of oligoastrocytomas). 15 Moreover, 1p deletions have been linked to a better response to radio-and chemotherapy as well as favorable prognosis in gliomas.…”
Section: Discussionmentioning
confidence: 99%